INNOVATIVE APPLICATION OF CHINESE KUNQU OPERA COSTUMES STYLE PRINCIPLES IN MODERN DESIGN - CHEN , S.; KROTOVA, T. (Art and Design, 2024)
Goal: an in-depth study of innovative practices of contemporary design based on the values of China's intangible cultural heritage, in particular, the use of formative and decorative characteristics and techniques of the Kunqu Opera stage costume in the creation of modern models of clothing for dressy or casual use. Methodology. The study uses historical, analytical, and chronological methods, as well as methods of formal and figurative-stylistic analysis. Results. Based on the systematization of documentary materials, the unique features of the costumes of the main characters in different scenes of the youth version of «The Peony Pavilion» opera have been studied. Formative and stylistic approaches have been generalized, and the characteristics of the costume, such as the Style of the main constituent elements (The headdress, Horse-face Skirt, Pleats, Cloak), as well as Colors and Patterns, have been integrated into the author's own design solution for the design of modern costumes for dress purposes. Based on the example of the contemporary Chinese designer MUKZIN's collection, the article shows how the integration of expressive possibilities of stage costumes can shape aesthetic trends in contemporary design and expand its creative potential. The scientific novelty of the study is to identify the expressive characteristics of the Kunqu Opera stage costume and to propose an approach for its integration into modern clothing. The integration of intangible cultural heritage values into modern trends not only expands the possibilities of design but also opens up a way to preserve traditional culture. Practical significance. The study of the artistic and aesthetic features of the costumes of the Kunqu Opera in the Youth Version of «The Peony Pavilion» and the application of innovative design approaches is an important area of creativity and research not only for designers but also for stage designers and art and fashion historians. The materials of the research can be used in educational courses as well as in costume design practices.